(untitled) (Medico Legal Update, 2021)
Introduction: Diabetic foot and complicated ulcers are relatively common occurrence in daily surgical to patient department for managing them various dressing materials and solutions are available. One of such is acriflavine emulsion. Case Presentation: Both patients were diabetic having large ulcers over leg 2nd was Hepatitis B positive also having large leg ulcer due to insect bite. In both Acriflavine emulsion was used as dressing material. STSG was performed in both and graft were accepted with uneventful post op course Discussion: Acriflavine made from acridine has a local antiseptic property with Antimicrobial and antiviral action it does have a skin irritant 1 property but to neutralise that glycerine was used in 1:1000 emulsion Conclusion: Acriflavine which was used in world war1 as antiseptic solution for war wounds can be used for dressing of complicated ulcers and wounds to gainbetter results.